2021
DOI: 10.1007/s12652-021-02902-w
|View full text |Cite
|
Sign up to set email alerts
|

Fermatean fuzzy CRITIC-EDAS approach for the selection of sustainable third-party reverse logistics providers using improved generalized score function

Abstract: In today’s world, the demand for sustainable third-party reverse logistics providers (S3PRLPs) becomes an increasingly considerable issue for industries seeking improved customer service, cost reduction and sustainability perspectives. However, the assessment and selection of right S3PRLP is a complex uncertain decision-making problem due to involvement of numerous conflicting attributes, imprecise human mind and lack of information. Recently, Fermatean fuzzy set (FFS) has been recognized as one of the suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 81 publications
1
57
0
Order By: Relevance
“…Like the Standard Deviation and Entropy methods, this method has also been developed in many research types and applied to different MCDM problems. Shipboard crane selection [51], healthcare management evaluation [52], configuration optimization in energy systems [53], supply chain risk management [54], financial risk evaluation [52], quality assessment of wireless networks [55], urban transportation [56], location planning [57], third-party logistics providers [58], air quality assessment [59], waste disposal [60], and outsourcing evaluation [61] are some of the recent and essential real-life problems in which the CRITIC method has been applied.…”
Section: Recent Studies On Objective Weighting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the Standard Deviation and Entropy methods, this method has also been developed in many research types and applied to different MCDM problems. Shipboard crane selection [51], healthcare management evaluation [52], configuration optimization in energy systems [53], supply chain risk management [54], financial risk evaluation [52], quality assessment of wireless networks [55], urban transportation [56], location planning [57], third-party logistics providers [58], air quality assessment [59], waste disposal [60], and outsourcing evaluation [61] are some of the recent and essential real-life problems in which the CRITIC method has been applied.…”
Section: Recent Studies On Objective Weighting Methodsmentioning
confidence: 99%
“…Table 1 presents a summary of the above-mentioned studies. [38] 2021 Standard Deviation Evaluation design parameters of solid ventilated brake disc Afshar et al [42] 2021 Entropy Subcontractor evaluation problem using type-2 fuzzy sets Wang et al [50] 2021 Entropy Supplier selection for battery swapping stations Peng et al [52] 2021 CRITIC Healthcare management evaluation Görçün [56] 2021 CRITIC Evaluation of metro and tram vehicle for urban transportation Mishra et al [58] 2021 CRITIC Selection of sustainable third-party reverse logistics providers Peng et al [52] 2021 CRITIC Financial risk evaluation…”
Section: Recent Studies On Objective Weighting Methodsmentioning
confidence: 99%
“…Aydemir and Gunduz [ 9 ] extended the Dombi aggregation operators for FFSs. Recently, Mishra et al [ 32 ] studied an integrated MCDM methodology by CRiteria Importance Through Intercriteria Correlation (CRITIC) and Evaluation Based on Distance from Average Solution (EDAS) approaches under FFS context. Nonetheless, no one has focused their attention on location selection for HCW disposal under FFSs context.…”
Section: Earlier Workmentioning
confidence: 99%
“…Chen et al [1] suggested a new multi-perspective multi-attribute decision-making support system for the evaluation and prioritization of 3PRLPs under an HF linguistic term set environment. Mishra et al [70] gave a combined framework with CRITIC and EDAS methods for Fermatean fuzzy sets (FFSs) to deal the S3PRLP selection problem in which the attributes and DEs' weights are completely unknown.…”
Section: Sustainable Third-party Reverse Logistics Provider (S3prlp) mentioning
confidence: 99%
“…Mishra et al [34,35] proposed some entropy and divergence measures for HFSs and applied them to a service quality assessment and green supplier selection problem, respectively. Kobza et al [70] studied a new axiomatic definition of HF divergence measure and proposed some divergence measures under an HFS context. Recently, Mishra et al [75] studied an HF divergence measure-based Additive Ratio Assessment approach for a COVID-19 medication problem.…”
Section: New Discrimination Measure For Hfssmentioning
confidence: 99%